Pottery of Manqabad : a selected catalogue of the ceramic assemblage from the monastery of 'Abba Nefer' at Asuyt (Egypt) - Incordino, Ilaria, (Access archaeology., 2020)
Ilaria Incordino's book presents a catalogue of selected pottery from the monastic site of Manqabad (Asyut, Egypt) as part of an ongoing study and conservation project at the University of Naples. The typologies identified include the most relevant Byzantine classes and a particular link with production from the Middle Egypt region.